Akuntabilitas Auditor dalam Perspektif Ajaran Karmaphala - Purnamasari, Dian; Kurniawati, Selly (Owner : Riset dan Jurnal Akuntansi, 2024)
The significance of an auditor's accountability is widely recognized in the execution of their professional duties. Numerous auditors encounter significant challenges stemming from the disregard of ethical principles, instances of error, and breaches of professional norms and codes of ethics. The concept of karmaphala, or cause and effect, is recognized in the Hindu religion. This study investigates the concept of auditor accountability via the lens of karmaphala teachings, building upon the aforementioned context. This study employs a qualitative methodology, specifically utilizing a library research strategy. The findings of the study indicate that auditors exhibit heightened diligence in their evaluation of facts, assumptions, and ethical boundaries while applying the karmaphala philosophy. This approach aims to prevent unethical conduct that may have adverse consequences for several stakeholders.